DETEKSI DAN PENGHITUNGAN KERAPATAN INOKULUM Phytophthora capsici DALAM TANAH DENGAN MENGGUNAKAN UMPAN DAUN LADA - BANDE, LA ODE SANTIAJI; HADISUTRISNO, BAMBANG; SOMOWIYARJO, SUSAMTO; SUNARMINTO, BAMBANG HENDRO (Jurnal Agroteknos, 2014)
Phytophthora capsiciis a causal agent for footrot disease in pepper and classified as a soil-borne pathogen. The inoculums of P. capsici in the soilis difficultto detect. The dynamics of P. capsici population in the soil is frequently and rapidly fluctuates and hard to detect, causing the pathogen to produce disease rapidly. The aimsof this research were todetect the pathogen P.capsici using black pepper leaf baiting and to quantify the inoculum of the pathogen P.capsici in the soil belonging to several disease intensities of the black pepper foot rot in the field. The first experiment: detecting the pathogen P. capsici using black pepper leaf baiting in the soil artificially infested using several sporangia, anda second experiment: quantification of propagul of the P.capsici in various categories of intensity on the black pepper foot rot disease in the field. The research results showed that the black pepper leaf baiting could be used to detect the existence of the propagul of P.capsiciin the soil artificially infested in various densities of sporangia. The increase in disease intensity occurred in parallel with the greater density of P. capsici inocula in soil. The density of P. capsici inocula in the soil tended to decline when the disease intensity reached the highest level.